O comportamento altruísta no jogo da partilha invertido - Zin, Gabriela de Oliveira (Universidade Federal de São Carlos, 2017)
Economic games are useful as experimental models of complex social interaction situations such as altruism. These games are important because they allow you to analyze the variables involved in people's decision making. However, the definition of altruism under the behavioral perspective is still imprecise, which hampers experimental control, with respect to both stimuli control, and with respect to response and reinforcement parameters. The present study sought to review the conceptual literature on the topic of altruism, seeking to elucidate the construction of this concept in Behavior Analysis and then propose an inverted model of the Sharing Game based on a conceptual refinement on the operationalization of altruism. Both the Inverted Sharing Game and the Traditional Sharing Game (Kennelly & Fantino, 2007) require participants to choose between two different amounts of money, one larger and one smaller for themselves and an anonymous participant. However, in the Sharing Game when the participant chooses the highest amount for himself, he ends up making an even bigger amount available to the other participant, and when he chooses the lowest amount of money for himself, he makes available to the other an even smaller amount. The Inverted Sharing Game, on the other hand, operates the opposite way, that is, when the participant chooses the largest amount of money for himself, provides a smaller amount to the second participant and, if he chooses the smallest amount for himself, the Another participant earns a larger amount. In a cross-subject design, experiments involving repeated attempts were made with twenty opportunities in which the participants chose how to distribute the resources between themselves and a passive participant. Two hundred participants were equally distributed under four conditions, one of which was the exposure to the Sharing Game, another to the Inverted Sharing Game, and the other two conditions were a junction between the two models presented in different orders. The experiment demonstrated that the number of self-controlled responses evoked by the Sharing Game is greater when compared to the Inverted Sharing Game, in addition to suggesting that there is an order effect of one game over the other. The study has social and scientific importance while presenting two experimental models to study the phenomenon of generosity or altruism, of particular interest in the scope of cooperation, its social importance and the survival of the species.
Altruistic behavior in the twisted sharing game
Keywords: Tomada de decisão; Altruísmo; Jogos econômicos; Jogo da partilha; Jogo da partilha invertido; Decision making; Altruism; Economic games; Sharing game; Inverted sharing game; CIENCIAS HUMANAS::PSICOLOGIA